The Longitudinal Evaluation of Familial Frontotemporal Dementia Subjects (LEFFTDS) Protocol: Framework and Methodology - Boeve, B (Alzheimers Dement, 2020)
INTRODUCTION: It is important to establish the natural history of familial frontotemporal lobar degeneration (f-FTLD) and provide clinical and biomarker data for planning these studies, particularly in the asymptomatic phase. METHODS: The Longitudinal Evaluation of Familial Frontotemporal Dementia Subjects protocol was designed to enroll and follow at least 300 subjects over at least three annual visits who are members of kindreds with a mutation in one of the three most common f-FTLD genes – microtubule associated protein tau, progranulin or chromosome 9 open reading frame 72. RESULTS: We present the theoretical considerations of f-FTLD and the aims/objectives of this protocol. We also describe the design and methodology for evaluating and rating subjects, in which detailed clinical and neuropsychological assessments are performed, biofluid samples are collected and MRI scans are performed using a standard protocol. DISCUSSION: These data and samples, which are available to interested investigators worldwide, will facilitate planning for upcoming disease-modifying therapeutic trials in f-FTLD.